ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN/KOTA PROVINSI JAWA TENGAH TAHUN 2009-2013 - Rosyid Adhi Santoso, 10.05.52.0103; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of GDP, inflation, population and the number of hotels to revenue (PAD) in the District / City Central Java. Source of data used are secondary data obtained from BPS Central Java during the years 2009 to 2013. Data were analyzed using multiple linear regression models is to determine each of the independent and dependent variable either simultaneously or partially. The results showed that each variable has the same effect of variable Gross Regional Domestic Product (GDP) inflation, and the number of hotel significant positive effect on local revenue (PAD), while the number of people positive effect on local revenue (PAD).Keywords: PAD, GDP, Inflation, Population, Number Of Hotels